PENGARUH DANA KAPITASI DALAM MENINGKATKAN KUALITAS LAYANAN PADA FASILITAS KESEHATAN TINGKAT PERTAMA DI YOGYAKARTA - Shofiyah, Indah; Bastian, Indra (Universitas Ahmad Dahlan, 2020)
This study aims to investigate the effect of capitation in improving the service quality at primary care in Yogyakarta province. Variables in this research are incentives and the proportion of capitation. This research use financial and performance primary care reports which collected from Health Agency in Yogyakarta Province. Data was successfully processed were 62 reports. The results of this research show that incentives and the proportion of capitation statistically influence in improving service quality, on the other side proportion of capitation funds statistically does not strengthen relationship between incentives and service quality.